2018
DOI: 10.1039/c8dt01234b
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular metal–ligand electron transfer triggered by co-ligand substitution

Abstract: The possibility of directed stimulation of intramolecular electron transfer between a metal and a redox-active ligand in a molecular coordination compound is the key to its application in molecular catalysis and other research themes. Although the stimulation by a substitution reaction of the co-ligands is often postulated as key step in catalytic cycles using redox-active ligands as electron reservoirs, there are only a few explicit examples for such reactions. Herein we report the synthesis of the first dica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…While such an behavior is a cornerstone in enzymatic reactions, the wide opportunities offered by these bioinspired approaches are only emerging and should blossom in the near future. In order to assert this field as a true game-changer in copper catalysis, further work should aim at rationalizing the "redox dialogue" between the metal and the ligand, and provide a deeper understanding of the valence tautomerism at work in such systems in order to develop predictive tools for reactivity control [41]. Such knowledge is most likely to result in new advances in the fast-expanding field of redox catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…While such an behavior is a cornerstone in enzymatic reactions, the wide opportunities offered by these bioinspired approaches are only emerging and should blossom in the near future. In order to assert this field as a true game-changer in copper catalysis, further work should aim at rationalizing the "redox dialogue" between the metal and the ligand, and provide a deeper understanding of the valence tautomerism at work in such systems in order to develop predictive tools for reactivity control [41]. Such knowledge is most likely to result in new advances in the fast-expanding field of redox catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, the oxidative cross-coupling reactiono fp henolsw ith a non-complementary relationship is studied in detail. Hence it was possible to shift electrons between the redox-active guanidine ligand and the coppera tom in ac omplex by changing the counterions, [35] the solvent [36][37][38] or the temperature. This ligand, which is oxidized reversibly at low potential( E 1/2 = À0.7 Vv s. Fc + /Fc in CH 2 Cl 2 solution for the redox couple 1 2 + + /1), [34] supplies the metal atom with extra electrondensity,u pt ot he point of full transfer of two electrons from the ligand to the two coppera toms.…”
Section: Introductionmentioning
confidence: 99%
“…This ligand, which is oxidized reversibly at low potential( E 1/2 = À0.7 Vv s. Fc + /Fc in CH 2 Cl 2 solution for the redox couple 1 2 + + /1), [34] supplies the metal atom with extra electrondensity,u pt ot he point of full transfer of two electrons from the ligand to the two coppera toms. An umber of studies [35][36][37][38][39][40][41] have shown that the particularly low barrierf or intramolecular ligand-metal electron transfer in guanidine-copper complexes is due to the structural harmonization betweenC u II and Cu I complexes causedb yt he p-donor properties of the guanidine ligands( see also work by Herres-Pawlis et al on the entatic state concept in this context [42][43][44][45][46] ). Hence it was possible to shift electrons between the redox-active guanidine ligand and the coppera tom in ac omplex by changing the counterions, [35] the solvent [36][37][38] or the temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25.3 for (1 + H) + in CH 3 CN sharplyd ecreasesu pon oxidation. Interestingly,g reen 1 2 + stilli saLewis [35] and Brønsted base, and is protonated with HBF 4 ·Et 2 Ot ob lue (1 + H) 3 + and orange (1 + 2H) 4 + (with ap K a value of ca. 13 in CH 3 CN close to CF 3 COOH,S cheme 1).…”
mentioning
confidence: 99%